"Macromolecules – ghosts" in dynamic light scattering analysis: An approach to study interaction between CdSe quantum dots and RAFT-based poly(methyl methacrylate). (25th April 2018) - Litmanovich, E.A.; Bekanova, M.Z.; Shandryuk, G.A.; Chernikova, E.V.; Talroze, R.V.
Abstract: Poly (methyl methacrylate) samples with low dispersities and given molecular weights are synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization using cyano-4-(phenylcarbonothioylthio)pentanoic acid and S-(2-cyano-2-propyl)-S-dodecyl trithiocarbonate. The reduction of the terminal thiocarbonylthio group in the polymer results in the production of two group of samples which contain either one (thiol or carboxylic) or two (carboxylic and thiol) terminal groups capable of interaction with CdSe quantum dots. An approach of the "macromolecules – ghosts" based on the isorefractivity of poly (methyl methacrylate) in toluene was used to study formation of the complexes between end-functionalized macromolecules and quantum dots. Correlation between end-functionality, molecular weight of the polymer and the size of the complexes is discovered. Graphical abstract: Image 1 Highlights: RAFT-based PMMA with SH and/or COOH terminal groups are synthesized. Both kinds of chain terminal groups are capable of interaction with CdSe QDs. DLS and macromolecules-ghosts approach indicate the formation of QD–PMMAcomplex. PMMA chains in the complex with QD have the conformation of the swollen coil.